DEVELOPMENT OF STEAM-BASED E-HANDOUT TO IMPROVE MATHEMATICAL CONNECTION SKILLS AT UPT SMP NEGERI 41 MEDAN - Siti Nurjannah; Rosliana Siregar; Syahlan (Jurnal PAJAR (Pendidikan dan Pengajaran), 2023)
This paper discusses an e-handout of STEAM-based circle material to improve mathematical connection skills at UPT SMP Negeri 41 Medan. The research and development design (R&D) uses the Thiagarajan model. The research results imply that the STEAM-based e-handout met the criteria of valid, practical, and improved mathematical connection skills. Material experts provided an average score of 81% (very valid), linguists provided an average of 80% (fairly valid), and media experts provided an average score of 100% (very valid). The average score of the teacher's response to the practicality of the e-handout was 75% (practical) and the student's percentage was 67% (practical), which means that teachers and students have a positive response. Mathematical connection skills at UPT SMP Negeri 41 Medan met the criteria of effectiveness. It is shown in the second trial in which the learning objectives that were achieved from the three mathematical connection indicators exceeded 75% and students’ learning completeness was 96%. The improvement in students' mathematical connection skills with an average N-gain score in trial I and trial II indicate an improvement score of 0.134. It can be concluded that the developed e-handout is valid, practical, and effective, as well as it can improve mathematical connection skills.